Tindak Pidana Penipuan Diskon Palsu dalam E-Commerce: Kajian Hukum dan Perlindungan Konsumen di Indonesia - Kinarta, Danny; Myharto, Wiend Sakti (PT Elaborium Elevasi Indonesia, 2025)
This research examines the legal framework and consumer protection concerning fake discount fraud in e-commerce in Indonesia, a growing issue alongside the rapid expansion of online transactions. Employing a normative legal research methodology and literature review, this study analyzes relevant Indonesian laws, including the Electronic Information and Transactions Law (UU ITE) and the Consumer Protection Law (UUPK). The findings reveal that while legal provisions exist to address such deceptive practices, challenges in enforcement and a lack of awareness among both merchants and consumers persist. This research concludes by emphasizing the need for enhanced legal enforcement, greater platform accountability, and improved consumer education to combat fake discount fraud effectively in Indonesia's digital marketplace.